Association Between NAT2 Polymorphism and Lung Cancer Risk: A Systematic Review and Meta-Analysis - Zhu, Ke; Xu, Aiqun; Xia, Wanli; Li, Pulin; Zhang, Binbin; Jiang, Huihui; Zhou, Sijing; Wang, Ran (Frontiers in Oncology, 2021)
Lung cancer is the leading cause of cancer-related death worldwide and has a high incidence rate. N-Acetyltransferase 2 (NAT2) is a polymorphic xenobiotic enzyme, which can catalyze N-acetylation and O-acetylation of various carcinogens such as aromatic, heterocyclic amines and hydrazines. At present, many studies have explored the effects of NAT2 polymorphism on lung cancer, but we found inconsistent results. We researched 18 published studies, involving 4,016 patients and 5,469 controls, to more accurately assess the effects of NAT2 polymorphism on lung cancer risk and to investigate whether smoking is associated. We used STATA software to analyze the extracted data and used STATA for subgroup analysis, sensitivity analysis, and to perform publication bias tests. To determine the correlation, we used the crude odds ratio (ORs) with 95% confidence interval (CIs). Our study was prospectively registered in PROSPERO (CRD42020159737). The odds ratio was 1.53 (95% CI: 1.21–1.95, I² = 45.2%, P=0.104) for the NAT2 slow + intermediate phenotype versus rapid phenotype. The results suggested that people with NAT2 non-rapid (slow + intermediate) phenotype have a significantly increased risk of lung cancer. In addition, NAT2 rapid phenotype was significantly associated with reduced risk of lung cancer, compared with slow phenotype or intermediate phenotype (slow phenotype vs. rapid phenotype: OR: 1.61, 95% CI: 1.07–2.42, I²= 50%, P= 0.075; intermediate phenotype vs. rapid phenotype: OR: 1.47, 95% CI: 1.15–1.88, I²= 40.3%, P= 0.137).